2019
DOI: 10.12659/msm.911697
|View full text |Cite|
|
Sign up to set email alerts
|

Xanthoxyletin Inhibits Proliferation of Human Oral Squamous Carcinoma Cells and Induces Apoptosis, Autophagy, and Cell Cycle Arrest by Modulation of the MEK/ERK Signaling Pathway

Abstract: BackgroundThis study aimed to investigate the effects of xanthoxyletin, a plant-derived coumarin, on human oral squamous cancer cells in vitro and in mouse xenografts in vivo.Materia/MethodsThe study included SCC-1 human oral cancer cells and EBTr normal embryonic bovine tracheal epithelial cells, which were treated with 0 μM, 5 μM, 10 μM, and 20 μM of xanthoxyletin for 24 hours. The MTT assay assessed cell viability, and autophagy was detected by electron microscopy. Cell apoptosis was investigated using 4′,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Cell proliferation is predominantly regulated by the cell cycle, which is a complex network of regulatory process involving multiple signaling pathways ( 19 ). For example, T-Box transcription factor TBX3 has been indicated to function as an immortalizing gene promoting proliferation via actively repressing negative cell cycle regulators, which has been associated with the c-Myc-mediated pathway ( 20 ). Moreover, xanthoxyletin has been revealed to inhibit proliferation and induce cell cycle arrest via modulating the MEK/ERK signaling pathway ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell proliferation is predominantly regulated by the cell cycle, which is a complex network of regulatory process involving multiple signaling pathways ( 19 ). For example, T-Box transcription factor TBX3 has been indicated to function as an immortalizing gene promoting proliferation via actively repressing negative cell cycle regulators, which has been associated with the c-Myc-mediated pathway ( 20 ). Moreover, xanthoxyletin has been revealed to inhibit proliferation and induce cell cycle arrest via modulating the MEK/ERK signaling pathway ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, T-Box transcription factor TBX3 has been indicated to function as an immortalizing gene promoting proliferation via actively repressing negative cell cycle regulators, which has been associated with the c-Myc-mediated pathway ( 20 ). Moreover, xanthoxyletin has been revealed to inhibit proliferation and induce cell cycle arrest via modulating the MEK/ERK signaling pathway ( 20 ). Thus, the effect of TC2N on cell cycle progression and cell cycle-related proteins was further determined The experimental results revealed that TC2N overexpression increased the percentage of cells in the S phase, and upregulated the expression levels of cyclin D1, cyclin E1 and CDK4, while TC2N knockdown achieved the opposite effects.…”
Section: Discussionmentioning
confidence: 99%
“…The xenograft model was constructed as previously described with minor modification. 20 In brief, approximately 1 × 10 6 BcaCD885 cells were subcutaneously inoculated into the flanks of each mouse. When tumor volume reached ~50 mm 3 , all mice were randomly divided into two groups (n = 8): vehicle group and control group.…”
Section: Xenograft Modelmentioning
confidence: 99%
“…Esculetin (20 µM) was also demonstrated to be able to suppress the proliferation of human leukemia HL-60 cells, through the induction of apoptosis, autophagy, and the arrest of the cell cycle and the Raf/Mitogen-activated protein kinase/ERK kinase (MEK)/ERK signaling pathway [195]. Similarly, xanthoxyletin (5-20 µM) inhibited the growth of SCC-1 cells by modulating MEK/ERK pathway, and by inducing apoptosis, autophagy and cell cycle arrest [196]. Recently, it was shown that osthole (7-metoxy-8-isopenthenocoumarin; 150-250 µM), alone and with TMZ, triggered autophagy in human glioblastoma multiforme (T98G) and anaplastic astrocytoma (MOGGCCM) cells, although the main type of induced death in these cells was apoptosis [197].…”
Section: Coumarinsmentioning
confidence: 99%